Newlavirus, a Novel, Highly Prevalent, and Highly Diverse Protoparvovirus of Foxes ( Vulpes spp.) - Marta Canuti; Émilie Bouchard; Bruce Rodrigues; Hugh G. Whitney; Marti Hopson; Cornelia Gilroy; Garry Stenson; Suzanne C. Dufour; Andrew S. Lang; Joost T. P. Verhoeven (Viruses, 2021)
The genus Protoparvovirus (family Parvoviridae ) includes several viruses of carnivores. We describe a novel fox protoparvovirus, which we named Newlavirus as it was discovered in samples from Newfoundland and Labrador, Canada. Analysis of the full non-structural protein (NS1) sequence indicates that this virus is a previously uncharacterized species. Newlavirus showed high prevalence in foxes from both the mainland (Labrador, 54/137, 39.4%) and the island of Newfoundland (22/50, 44%) but was not detected in samples from other carnivores, including coyotes ( n = 92), lynx ( n = 58), martens ( n = 146), mink ( n = 47), ermines ( n = 17), dogs ( n = 48), and ringed ( n = 4), harp ( n = 6), bearded ( n = 6), and harbor ( n = 2) seals. Newlavirus was found at similar rates in stool and spleen (24/80, 30% vs. 59/152, 38.8%, p = 0.2) but at lower rates in lymph nodes (2/37, 5.4%, p < 0.01). Sequencing a fragment of approximately 750 nt of the capsid protein gene from 53 samples showed a high frequency of co-infection by more than one strain (33.9%), high genetic diversity with 13 genotypes with low sequence identities (70.5–87.8%), and no geographic segregation of strains. Given the high prevalence, high diversity, and the lack of identification in other species, foxes are likely the natural reservoir of Newlavirus, and further studies should investigate its distribution.